Effect of stretching protocols on glenohumeral-joint muscle activation in elite table tennis players - Kazemi, O.; Letafatkar, A.; Marchetti, P. H. (International Journal of Sports Physiology and Performance, 2021)
Context: Several studies report static-stretch-induced deficits and dynamic-stretch performance improvement after intervention. Purpose: To investigate the muscle activation of the forehand and backhand in table tennis players after experiencing static- and dynamic-stretching protocols. Methods: A total of 24 elite male table tennis players (age 22.7 [3.46] y, height 1.78 [0.03] m) were tested before and 0, 10, 20, and 30 min after the 3 conditions (dynamic stretch, static stretch, and no stretch). The MEGA ME6000 (Mega Electronics, Kuopio, Finland) was used to capture the surface EMG data of the anterior deltoid, middle deltoid, posterior deltoid, biceps, and triceps muscles. Muscle activation data of the pretest were compared with posttest 0, 10, 20, and 30 min. These data were also compared between 3 different conditions (dynamic stretch, static stretch, and no stretch). Results: A 2-way repeated-measures analysis of variance indicated significant differences in the forehand and backhand, and Bonferroni test as a post hoc comparison revealed significant differences between the pretest and posttests in several muscles (P < .05). Furthermore, there were significant differences in the posttest between the 3 conditions (P < .05). Conclusions: In general, there was a short-term effect of static- and dynamic-stretching protocols on glenohumeral-joint muscle activation in elite table tennis players. The static and dynamic stretching presented a decrease and increase, respectively, in muscle activation up to 30 min after stretching. In conclusion, the additive and subtractive effects of dynamic- and static-stretching protocols on muscle activation seem to persist after 30 min.